2008
DOI: 10.5194/bg-5-1411-2008
|View full text |Cite
|
Sign up to set email alerts
|

The CO<sub>2</sub> exchange of biological soil crusts in a semiarid grass-shrubland at the northern transition zone of the Negev desert, Israel

Abstract: Abstract. Biological soil crusts (BSC) contribute significantly to the soil surface cover in many dryland ecosystems. A mixed type of BSC, which consists of cyanobacteria, mosses and cyanolichens, constitutes more than 60% of ground cover in the semiarid grass-shrub steppe at Sayeret Shaked in the northern Negev Desert, Israel. This study aimed at parameterizing the carbon sink capacity of welldeveloped BSC in undisturbed steppe systems. Mobile enclosures on permanent soil borne collars were used to investigat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 34 publications
(46 reference statements)
8
43
0
Order By: Relevance
“…The main difference we could find in these studies was the thickness of the biocrust plus the sub-crust (soil) layer used. While the studies revealing biocrusts to be CO 2 emitters used collars penetrating 20 to 35 cm into the soil (Bowling et al, 2011;Su et al, 2013;Darrouzet-Nardi et al, 2015), the studies attributing biocrusts to be CO 2 gainers during the course of 1 year either used pieces of biocrust of 1 to 5 cm thickness (this study; Brostoff et al, 2005;Feng et al, 2014), or a collar penetrating only 5.5 cm into the soil (Wilske et al, 2008(Wilske et al, , 2009). The metabolic activity of heterotrophic organisms as well as respiration of roots from nearby plants of deeper soil levels apparently influence the CO 2 gas exchange measurements accordingly as indicated in the investigation of Bowling et al (2011).…”
Section: Seasonality and Co 2 Balancesmentioning
confidence: 99%
See 4 more Smart Citations
“…The main difference we could find in these studies was the thickness of the biocrust plus the sub-crust (soil) layer used. While the studies revealing biocrusts to be CO 2 emitters used collars penetrating 20 to 35 cm into the soil (Bowling et al, 2011;Su et al, 2013;Darrouzet-Nardi et al, 2015), the studies attributing biocrusts to be CO 2 gainers during the course of 1 year either used pieces of biocrust of 1 to 5 cm thickness (this study; Brostoff et al, 2005;Feng et al, 2014), or a collar penetrating only 5.5 cm into the soil (Wilske et al, 2008(Wilske et al, , 2009). The metabolic activity of heterotrophic organisms as well as respiration of roots from nearby plants of deeper soil levels apparently influence the CO 2 gas exchange measurements accordingly as indicated in the investigation of Bowling et al (2011).…”
Section: Seasonality and Co 2 Balancesmentioning
confidence: 99%
“…For example, a cyanobacteriadominated biocrust in the Mojave Desert, USA, had a C gain of 11.5 g m −2 yr −1 (Brostoff et al, 2005), 6.7 times higher than the cyanobacteria-dominated Boodjamulla biocrust. Another biocrust dominated by cyanobacteria, algae, lichens and mosses from the Negev Desert, Israel, resulted in a C gain of 0.7 to 5.1 g m −2 yr −1 (Wilske et al, 2008(Wilske et al, , 2009) and thus is pretty close to what we observed in our study, which also corresponds with the results from biocrusts composed of cyanobacteria, lichens and mosses of the Mu Us Desert in China with a C gain of 3.5 to 6.1 g m −2 yr −1 (Feng et al, 2014).…”
Section: Seasonality and Co 2 Balancesmentioning
confidence: 99%
See 3 more Smart Citations